نمذجة حاقن بخاري تفريغي بطريقةCFD ودراسة تغير بارامترات الجريان داخله. - عساف, سهام (Latakia University Journal -Engineering Sciences Series, 2014)
تعد عملية التصميم والتحليل للآلات الميكانيكية عملية مكلفة وتحتاج وقتاً طويلاً وإمكانات كثيرة للوصول إلى التصميم الأمثل الممكن استثماره صناعيا, لذلك فإن تقنية CFDتوفر رديفاً قويّاً للمخابر البحثية لأنها أكثر فعّالية وأقلّ كلفة, ويعمل على محاكاة الظواهر الفيزيائية المعقدة للموائع التي يصعب اختبارها عن طريق التجارب. يهدف هذا البحث إلى تصميم حاقن بخاري بطريقة CFD ودراسة توزع البارامترات E,P,V,T,ρ ورقم ماخ ضمن الحاقن, دراسة تأثير سرعة التيار المحرﱢض Motive stream على الجريان ضمن الحاقن, حيث تمّت دراسة تغيّرات السرعة لهذا الجريان من (170-1000m/s), ودراسة تأثير قطر فوهة اختناق الحاقن على بارامترات الجريان ضمن المجال [Dn/Din =(0.01-0.09)], ودراسة تأثير سرعة التيار المتحرﱢض propelled stream على بارامترات الجريان ضمن الحاقن. لقد تبين أن سرعة الجريان تزيد بإنقاص نسبة الأقطار و بزيادة الضغط أيضاً. The design and analysis of mechanical machines is an expensive process and it needs a lot of time and abilities to reach the possible perfect design which can be adapted industrially. The technique of CFD is a strong supporter to research laboratories being more effective and less inexpensive, and it works to solve the complex physical phenomena of fluids which are difficult to examine through experiments. This research aims to design a steam jet using CFD the change of the flow of parametrates inside and Mach inside the jet. the research also aims to study the effect of the motive stream on the flow inside the jet. The study of the speed changes of this flow has been examined from (170-1000m/s) and the study of the diameter jet nosel effect on the parametrates flow within [Dn/Din =(0.01-0.09)] and finly the study the of the effect of propelled stream speed on the parametrates flow inside the jet.the motive velocity increases from during lower diameter ratio and the motive velocity increases from during increases the pressure.